Introductory Note to the Article “Aspetti e problemi della ricerca biblioteconomica di Luigi Balsamo” - Salarelli, Alberto (JLIS.it, 2020)
The purpose of this contribution is to introduce Luigi Balsamo’s article “Aspetti e problemi della ricerca biblioteconomica” originally published in «Bollettino d’informazioni. Associazione Italiana Biblioteche» (vol. 14, n. 1, 1974). Taking into consideration the situation in Italy of that time, Balsamo’s article highlights the limitations of the research in the LIS field, especially in comparison with foreign experiences in the same disciplinary area, as well as a substantial lack of government policy for libraries. Balsamo’s article also outlines a future development perspective for librarianship based on the close relationship that must exist between university and profession: the relationship between these two areas can act as a stimulus for the implementation and improvement of public library services, also in relation to the development of regional autonomies in the field of cultural heritage which, precisely in those years, began to take shape.